Acute effects of static and dynamic stretching on leg flexor and extensor isokinetic strength in elite women athletes - Sekir, U.; Arabaci, R.; Akova, B.; Kadagan, S. M. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The aim of this study was to explore the effects of static and dynamic stretching of the leg flexors and extensors on concentric and eccentric peak torque (PT) and electromyography (EMG) amplitude of the leg extensors and flexors in women athletes. Ten elite women athletes completed the following intervention protocol in a randomized order on separate days: (a) non-stretching (control), (b) static stretching, and (c) dynamic stretching. Stretched muscles were the quadriceps and hamstring muscles. Before and after the stretching or control intervention, concentric and eccentric isokinetic PT and EMG activity of the leg extensors and flexors were measured at 60 and 180°/s. Concentric and eccentric quadriceps and hamstring muscle strength at both test speeds displayed a significant decrease following static stretching (P<0.01-0.001). In contrast, a significant increase was observed after dynamic stretching for these strength parameters (P<0.05-0.001). Parallel to this, normalized EMG amplitude parameters exhibited significant decreases following static (P<0.05-0.001) and significant increases following dynamic stretching (P<0.05-0.001) during quadriceps and hamstring muscle actions at both concentric and eccentric testing modes. Our findings suggest that dynamic stretching, as opposed to static or no stretching, may be an effective technique for enhancing muscle performance during the pre-competition warm-up routine in elite women athletes.